3D hierarchical CuO mesocrystals from ionic liquid precursors: towards better electrochemical performance for Li-ion batteries. Issue 21 (11th May 2016) - Duan, Xiaochuan; Huang, Hui; Xiao, Songhua; Deng, Jiwei; Zhou, Gang; Li, Qiuhong; Wang, Taihong
Abstract : 3D hierarchical CuO mesocrystals have been prepared from ionic liquid precursors under hydrothermal conditions, and exhibited superior electrochemical performance as anode materials, which offers a facile route for designing high-performance electrodes for Li-ion batteries. Abstract : CuO mesocrystals have been synthesized by nonclassical crystallization in the presence of an ionic liquid and n -butylamine under hydrothermal conditions. The resultant mesocrystals are composed of anisotropic nanosheets and nanorods as building blocks and possess distinct 3D hierarchical superstructure exposed 001 crystal planes. The mechanisms underlying the sequential formation of the mesocrystals are as follows: amorphous particles first appeared under a high degree of supersaturation according to the Ostwald rule of stages; then, nanosheet subunits were favored to form due to the protection of the 001 planes by n -butylamine molecules and etching of the 010 planes by a hydrolysis reaction, leading to the formation of a large number of dangling bonds in the 010 planes. Therefore, the ionic liquid can interact with these primary particles to facilitate a self-assembled superstructure by π–π interactions along the [010] direction due to the highly ionic nature, resulting in a 3D framework structure of primary particles composed of nanosheet and nanorod subunits by oriented attachment. Moreover, owing to the inherent porosity associated with well-defined nanoparticle orientation, the 3D hierarchical CuO mesocrystals achieved a higher electrochemical property as anodes for Li-ion batteries, surpassing the performance of CuO nanosheets and CuO nanorods. The unique characteristics of the hierarchical mesostalline electrodes show an ideal geometry to form a stable SEI film, which offers a facile route for designing high-performance electrodes for long-life Li-ion batteries.